Analisis Penerapan Akuntansi Musyarakah terhadap PSAK 106 pada Bank Syariah X - Yusuf, Muhammad (Binus Business Review, 2012)
Islamic accounting standard is necessary in order to support the development of Islamic banking since it becomes the key to success standard Islamic bank in serving the community. Information provided by Islamic banks can be either financial reports or information of Islamic banking products. Broadly speaking, these products funding and lending of Islamic banks mobilize funds are grouped in a scheme consisting of the principles of Islamic banks are wadiah financing and mudarabah financing. The research focuses on the profit and loss sharing scheme, particularly the Musharakah financing. This research is to compare between theoryÂ and practice prevailing in the company, especially in the accounting treatment and measurement of the Musharaka Islamic Bank X, about whether or not the accounting treatment in accordance with PSAK 106. Accounting Musharaka. The results of this study suggest that accounting Applied Islamic Bank X, are in accordance with PSAK 106, only in writing the name of the estimates in recording with financing terms should be replaced with Musharaka investment.